Blood Lymphocyte Subsets for Early Identification of Non-Remission to TNF Inhibitors in Rheumatoid Arthritis - Rodríguez-Martín, Eulalia; Nieto-Gañán, Israel; Hernández-Breijo, Borja; Sobrino, Cristina; García-Hoz, Carlota; Bachiller, Javier; Martínez-Feito, Ana; Navarro-Compán, Victoria; Lapuente-Suanzes, Paloma; Bonilla, Gema; Pascual-Salcedo, Dora; Roy, Garbiñe; et al. (Frontiers in Immunology, 2020)
Background: TNF inhibitors (TNFis) are widely used for the treatment of rheumatoid arthritis (RA), although the response rates to this therapy in patients with RA remains heterogeneous and less than 50% achieve remission (REM). Objective: To analyze baseline peripheral blood leukocytes profiles in order to search for biomarkers identifying patients who will most likely not achieve REM under TNFi treatment. Methods: A prospective bi-center pilot study including 98 RA patients treated with TNFis and followed-up during 6 months. Patients were classified according to DAS28 as follows: those who achieved REM (DAS28≤2.6) and those who did not (DAS28>2.6) at 6 months after starting TNFis. These rates were also assessed by simplified disease activity index (SDAI ≤3.3 and SDAI>3.3, respectively). Peripheral blood immune cells were studied by flow cytometry before treatment initiation. Results: At 6 months, 61% or 80% of patients did not achieve REM by DAS28 or SDAI, respectively. Basal leukocyte profiles differed between REM versus non-REM patients. Non-REM patients showed lower percentages of total and naïve B cells at baseline than REM subjects. A B lymphocyte/CD4+ lymphocyte ratio (BL/CD4 ratio) <0.2 clearly associated with a higher probability of non-REM status based on DAS28 at 6 months (OR=9.2, p=0.006). These data were confirmed when patient response was evaluated by SDAI index. Conclusion: Our results strongly suggest that BL/ CD4 ratio could be considered as a useful biomarker for the early identification of non-remitters to TNFi in clinical practice.